Actual relevance of the first biography of sor Juana Inés de la Cruz (Estudios de Historia de España, 2021)
A study on the first biography of the novohispanic writer sor Juana Ines de la Cruz with unreliable data that was appointed by Jesuit Diego Calleja (1700), her fist biographer. Erroneous data was incorporated; like her father origin Basque, the incorrect date of birth and the erroneous circumstance of her final and death, etc., but documents located in 2016 testify that his father’s family came from Las Palmas de Gran Canaria in 1598; her real birth date is 1648 (no 1651), and where she died there was not urban epidemic.
Keywords: Juana Inés de la Cruz; Baroque literature; New Spain; Canarias